2003
DOI: 10.1029/2002ja009519
|View full text |Cite
|
Sign up to set email alerts
|

Local time distribution of net field‐aligned currents derived from high‐altitude satellite data

Abstract: [1] In order to explain features of geomagnetic disturbances observed at low and middle latitudes such as the dawn-dusk asymmetry in the north-south component, an antisunward current system has been proposed. The antisunward current system consists of net downward field-aligned currents on the dayside, antisunward auroral electrojet currents, and net upward field-aligned currents on the nightside. However, the net field-aligned currents consisting in this current system have not been established by spacecraft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Most of the current closure takes place via local Pedersen currents within the auroral zone flowing between the upward and downward FACs. However, observations show that there is generally an imbalance in total currents between the pair of opposite flowing R1 and R2 FACs in either dawnside or duskside, i.e., the total current flowing in R1 FCAs is more than that in R2 FACs [ Iijima and Potemra , 1976; Sugiura and Potemra , 1976; Fujii et al , 1981, 1994; Stauning and Primdahl , 2000; Fujii and Iijima , 1987; Nakano et al , 2002; Nakano and Iyemori , 2003; Christiansen et al , 2002]. Thus, there are net currents into (out of) the ionosphere due to the R1‐R2 imbalance in the dawnside (duskside) auroral region.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current closure takes place via local Pedersen currents within the auroral zone flowing between the upward and downward FACs. However, observations show that there is generally an imbalance in total currents between the pair of opposite flowing R1 and R2 FACs in either dawnside or duskside, i.e., the total current flowing in R1 FCAs is more than that in R2 FACs [ Iijima and Potemra , 1976; Sugiura and Potemra , 1976; Fujii et al , 1981, 1994; Stauning and Primdahl , 2000; Fujii and Iijima , 1987; Nakano et al , 2002; Nakano and Iyemori , 2003; Christiansen et al , 2002]. Thus, there are net currents into (out of) the ionosphere due to the R1‐R2 imbalance in the dawnside (duskside) auroral region.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an eastward/westward disturbance in the northern/southern hemisphere over the entire nightside is also common at midlatitudes (hereafter we will refer to eastward disturbances in the northern hemisphere and westward disturbances in the southern hemisphere as “positive” east‐west disturbances) [e.g., Iyemori , 1990; see also Yamashita et al , 2002]. These positive disturbances have been explained as a superposition of the effects of the Region 1 current system and those of the Region 2 current system by Nakano and Iyemori [2003].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Nakano and Iyemori (2003) showed that during magnetic storms, the magnitude of region 2 FACs was comparable with region 1 currents in the postnoon and premidnight sectors and, thus, the net contribution of the region 1 and 2 FACs was small. This finding supports the experimental result conducted by Nagai (1982) who found that no appreciable variations in the dayside geosynchronous magnetic field are associated with the Birkeland currents during geomagnetic storms.…”
Section: Discussionmentioning
confidence: 92%